TRIGONOMETRIYALÍQ TEŃLEMELERDI SHESHIWDE AYÍRÍM KORENLERDIŃ JOǴALÍP KETIW JAǴDAYLARÍN ANÍQLAW USÍLLARÍ - Djumabaev, N.; Qalekeeva, S.T. (SCIENCE and SOCIETY, 2021)
The article describes methods for solving some trigonometric equations for root loss. In the following formulas of trigonometric equations, you can see that the areas of the left and right are different.